Serum paraoxonase (a high-density lipoprotein-associated lipophilic antioxidant) activity in clinical follow-up of patients with acute pancreatitis, with particular emphasis on oxidative stress parameters and lipid profile: a prospective pilot trial. Issue 1 (1st January 2019) - Yuksekdag, Sema; Yuksel, Esra; Topcu, Ahmet; Karaagac, Neslihan; Uzun, Hafize; Kiziler, Ali Riza; Ezberci, Fikret; Unal, Ethem
ABSTRACT: The purpose of this study was to investigate the possible role of PON-1, an antioxidant lipophilic enzyme linked to HDL-C (high-density lipoprotein cholesterol), on the pathophysiology and clinical follow-up of acute pancreatitis. Biochemical tests, PON-1 and oxidative stress parameters (malonyl dialdehyde, MDA; superoxide dismutase, SOD; total antioxidant capacity, TAC) were evaluated in the sera of patients with acute pancreatitis at admission (day 0), day 3 and day 10 of follow-up, between June and September 2017. SPSS 13.0 statistical software package programme was used for statistical analyses.Mean age was 51.4 of the total 25 patients. Ranson scores were 0–1 points (60%), 3–4 points (24%) and 5–6 points (16%). CTSI (computed tomography severity index) scores were calculated, and most of the patients were seen to have mild or average pancreatitis (96%). While total cholesterol, triacylglycerol and LDL-C (low-density lipoprotein) levels stayed in their normal limits, there was a significant decrement tendency. HDL-C level was seen to rise significantly above its upper limit at day 10 ( p < 0.001). Mean PON-1 levels were measured as 69.23, 76.72 vs. 113.15 U/mL at days 0, 3 and 10, respectively; and it was positively correlated with HDL-C ( p < 0.001). Serum SOD increased also in parallel with PON-1 (20.49 vs. 39.46 U/mL) while MDA level decreased significantly (3.9 vs. 2.28 μM, p < 0.001). TAC was seen to rise significantly after treatment (0.52 vs. 1.22 mM). In conclusion, decreased PON-1 and HDL-C together with antioxidants SOD and TAC at the early period of acute pancreatitis were seen to rise after treatment, while the previously higher MDA level decreased in parallel. This reveals the importance of the balance between oxidative stress and antioxidant defense mechanisms in clinical progression of the disease, and the potential of PON-1 as a promising clinical marker.